2020
DOI: 10.30539/ijvm.v44i1.931
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Field Isolates of Infectious Bursal Disease Virus in Iraqi Farms

Abstract: Sixty samples of bursa of Fabricius were collected from broiler chickens suspected to be infected with infectious bursal disease virus (IBDV) in different areas of Iraq. The extracted nucleic acid was amplified using reverse transcriptase polymerase chain reaction (RT-PCR) targeting genes of segment A (Vp2, Vp3, Vp4 and Vp5 genes) and segment B (VP1 genes). The products of amplification were sent to Korea for sequencing using Sanger method. The sequencing analysis of the IBDV from the Iraqi isolates revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Therefore, these results agreed with Cheggag et al [49], who reported that this technique could detect highly virulent IBDV strains from classic and variant IBDV strains. These results also agree with Jumaa et al [50], who confirmed the VP2 of Iraqi vvIBDV strain using sequence analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, these results agreed with Cheggag et al [49], who reported that this technique could detect highly virulent IBDV strains from classic and variant IBDV strains. These results also agree with Jumaa et al [50], who confirmed the VP2 of Iraqi vvIBDV strain using sequence analysis.…”
Section: Discussionsupporting
confidence: 92%
“…These results also agree with Jumaa et al . [ 50 ], who confirmed the VP2 of Iraqi vvIBDV strain using sequence analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Birds from groups G3 and G2 had the highest prevalence of clinical symptoms and the highest rates of morbidity (both 100%), whereas birds from group G1 had the lowest incidence of clinical signs and the lowest rates of death (both 40 and 8%, respectively). The first group showed lower rates of compare the rates of morbidity and mortality to G2 and G3, which is consistent with Jumaa et al (11) who recorded that finding of cell-mediated immunity, though also linked to the immunopathogenesis of the virus, is crucial for the removal of IBDV and recovery. Rauf et al…”
Section: Morbidities and Mortalitysupporting
confidence: 88%
“…Along with renal alterations, there is an increase in gastrointestinal mucous. The surface of the bursa's serosal cavity is covered in a gelatinous, yellowish transudate in cases of severe dehydration, edema, and hyperemia (11,15).…”
Section: Mortalities and Morbidities Ratesmentioning
confidence: 99%